Management accounting systems,enterprise risk management and organizational performance: the case of financial institutions in Malaysia - Abdul Rasid, Siti Zaleha; Abdul Rahman, Abdul Rahim (2009)
In the latest development where organization functions are integrated with one another, management accounting systems (MAS), which function to provide information for decision making, should play an important role in risk management. Moreover, with the implementation of enterprise risk management (ERM), where risks are to be aggregated across different types of risk and across business units to obtain enterprise-wide risk situations, financial institutions are integrating their business lines performance management with risk management. Hence, management accounting systems which are crucial for control and performance management will be closely linked to risk management. The aim of this study is to explore the linkages between MAS, ERM and organizational performance by examining the MAS information characteristics that match the ERM implementation and the joint effects of MAS and ERM on organizational performance. The research method involved administering a questionnaire to 106 financial institutions listed on the Malaysian Central Banks website and the respondents are the chief financial officer (CFO) or the most senior positions in the finance department of the institutions. 16 post-survey semi-structured interviews were conducted with selected respondents. The findings from the survey and the post-survey interviews show that MAS and risk management complement each other. However, there was not enough evidence to fully support the role of risk management in enhancing the relationship between MAS and organizational performance. The post-survey interviews provide some insights into this issue.